THE EFFECTIVENESS OF THE USE OF E-LEARNING IN MULTIMEDIA CLASSES TO IMPROVE VOCATIONAL STUDENTS' LEARNING ACHIEVEMENT AND MOTIVATION - Alin Hoerunnisa; Nunuk Suryani; Agus Efendi (Kwangsan: Jurnal Teknologi Pendidikan, 2019)
The development of Information and Communication Technology (ICT) in education has paved the way for the emergence of new teaching and learning methodologies. E-learning, which refers to the use of ICT for learning purposes, is an important area emphasized in education. The purpose of this study was to determine the effectiveness of the use of E-learning in multimedia classes to improve vocational students' learning achievement and motivation. The Quasi-experiment method was used in this study. The research subjects used were class X students at the Veteran Vocational School Sukoharjo, Central Java. This research was conducted in Multimedia classes on computer and basic network subject matter on the topic of sharing devices. Class samples are selected using the random sampling technique. The experiment class consists of 31 students, while the control class consists of 33 students. In this study two formulation of problems were used, namely: (1) How is the effectiveness of E-learning to improve student learning achievement?; (2) How is the effectiveness of E-learning to improve student motivation? The hypothesis test used is the Independent T Test. The results showed that the use of E-learning can significantly improve student achievement and motivation on computer and basic network subject matter on the topic of sharing devices. In addition, the use of E-learning can also increase student participation in learning. AbstrakPerkembangan Teknologi Informasi dan Komunikasi (TIK) dalam pendidikan telah membuka jalan bagi munculnya metodologi pengajaran dan pembelajaran baru. E-learning, yang mengacu pada penggunaan TIK untuk tujuan pembelajaran, menjadi area penting yang ditekankan dalam pendidikan. Tujuan dari penelitian ini adalah untuk mengetahui efektifitas penggunaan E-learning untuk meningkatkan prestasi dan motivasi belajar siswa di Sekolah kejuruan. Metode kuasi ekperimen digunakan pada penelitian ini. Subjek penelitian yang digunakan yaitu siswa kelas X di SMK Veteran Sukoharjo, Jawa Tengah. Penelitian ini dilakukan di kelas Multimedia pada pelajaran komputer dan jaringan dasar pada topik sharing devices. Sampel kelas dipilih menggunakan teknik sampling acak. Kelas eksperimen terdiri dari 31 siswa, sedangkan kelas kontrol terdiri dari 33 siswa. Dalam penelitian ini digunakan dua rumusan masalah, yaitu: (1) Bagaimana keefektifan media E-learning untuk meningkatkan prestasi belajar siswa?; (2) Bagaimana keefektifan media E-learning untuk meningkatkan motivasi belajar siswa?. Uji hipotesis yang digunakan adalah Uji Independent T Test. Hasil dari penelitian ini menunjukkan bahwa penggunaan media E-learning secara signifikan dapat meningkatkan prestasi dan motivasi belajar siswa pada mata pelajaran komputer dan jaringan dasar pada topik sharing devices. Selain itu, penggunaan E-learning juga dapat meningkatkan partisipasi siswa terhadap pembelajaran.